Reported Policies, Guidance, and Related Resources for the Determination of Special Education and Related Services - Jennifer L. Kouo; Andrea R. Harkins-Brown
The Individualized Education Program (IEP) contains information that is critical to ensuring that a student with a disability (SWD) is receiving specially designed instruction as well as the appropriate related services and supports to make meaningful progress in the educational system. With varied practices across states, with some practices characterized by a formulaic approach rather than a student-centered decision-making process, the purpose of this review is to summarize the findings of currently available guidance related to determining the type and amount of special education and related services. This review aims to counteract practices that are not in alignment with the Individuals with Disabilities Education Act (IDEA), and to ensure that state and district guidance for IEP development promotes individualized development of special education and related services based on the unique needs of each student. The themes emphasize the importance of individualized, team-based, and flexible decision-making, the application of evidence-based practices, and ensuring clarity within the IEP. The article further presents the complexity of determining special education and related services while also recognizing the true constraints that exist and encroach upon student-centered and data-driven decisions made within IEP Teams.